The Investigation of Financial Reporting Practices Among Legal Established Small Medium-Sized Enterprises in Pontianak - B1034141022, Dewi Meliawaty (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
The aim of this study is to investigate the financial reporting practices among legal SMEs in Pontianak. This research use decriptive analysis method and investigated 187 SMEs by direct and indirect interview and self-answered questionnaire. Findings shows that 58% of SMEs in Pontianak prepare financial statements with 22% and 36% respectively prepares the complete four set with computerized and incomplete financial statement with manual accounting system.The computerized SMEs record keeping is in accordance with accounting cycle while the manual system was not. Most of the SMEs mentioned that they face no obstacles in preparing financial statement. SMEs in Pontianak prepared bookeeping and financial statement in simple form based on their understanding toward the accounting and facility they have.Â Keywords: Four-set financial statement, computerized accounting system, manual accounting system